2020
DOI: 10.1186/s13567-020-00821-w
|View full text |Cite
|
Sign up to set email alerts
|

Toward better control of classical swine fever in wild boars: susceptibility of boar-pig hybrids to a recent Japanese isolate and effectiveness of a bait vaccine

Abstract: We analyzed the pathogenicity of a recent Japanese classical swine fever virus (CSFV) to wild boars via an experimental infection using boar-pig hybrids as an alternative to wild boars. We also investigated the effectiveness of a bait vaccine against the CSFV. Naïve boar-pig hybrids and pigs showed clinical signs such as fever, leucopenia, anorexia and conjunctivitis following the experimental infection. In contrast, the boar-pig hybrids administered the bait vaccine did not show any clinical signs. Our data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…After each oral vaccination, wild boars with an antibody response induced by the oral vaccine were obtained in a proportional range of between 40% and 50% in weekly time points, describing the maintenance of the antibody-positive population in CSF affected areas. This statement demonstrates that the efficacy of the oral vaccine in wild boar supports the results of experimental studies of oral vaccines [ 21 , 30 ]. In terms of antibody response, wild boars assumed as being at a recovery status increased apparently after vaccination from 9% to 26%.…”
Section: Discussionsupporting
confidence: 76%
“…After each oral vaccination, wild boars with an antibody response induced by the oral vaccine were obtained in a proportional range of between 40% and 50% in weekly time points, describing the maintenance of the antibody-positive population in CSF affected areas. This statement demonstrates that the efficacy of the oral vaccine in wild boar supports the results of experimental studies of oral vaccines [ 21 , 30 ]. In terms of antibody response, wild boars assumed as being at a recovery status increased apparently after vaccination from 9% to 26%.…”
Section: Discussionsupporting
confidence: 76%
“…However, while the prevalence after vaccine distribution in Germany and France was less than 1% [ 12 , 32 ], 10% of animals in Japan remained infected after 1 year of vaccine distribution. Given the higher prevalence in Japan and lower pathogenicity of the causative strain [ 19 ], there would be a need for greater immunization levels to allow CSF eradication in the wild boar population in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Since infected wild boars pose a major infection risk to pig farms [ 18 ], there is a need to control CSF spread in wild boars to prevent its introduction to pig farms. An artificial infection study revealed that the recent Japanese isolate of the CSFV in wild boars was moderately virulent; moreover, the effectiveness of the bait vaccine was confirmed through an experimental CSFV challenge using boar-pig hybrids as a wild boar alternative [ 19 ]. However, characteristics of the affected wild boar population and the field effectiveness of the oral bait vaccination remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite strenuous control efforts, almost 2 year after the initial CSF notification, the lack of success in controlling the outbreak is concerning. The continuous notification of CSF in the area might have been attributed to wide spread of the virus within wild boar populations favored by free animal movements, as well as to the emergence of epidemiologically related domestic pig farms [ 76 , 230 ].…”
Section: Emergence Of New Csfv Subgenotype In Endemic Regions Undementioning
confidence: 99%